Deixis in the Movie of Spiderman (No Way Home): Pragmatic Analysis - Diani Rahmawati; Shinta Aziez (UM Purwokerto Press, 2023)
This study aims to identify the types and functions of deixis used in the movie Spiderman: No Way Home. This study used Spiderman: No Way Home as the object. This study used a qualitative approach. The writer used Levinson's (1983) theory to analyze the data. In the study of deixis in the movie Spiderman: No Way Home, it was found that there are five types of deixis consisting of person, place, time, discourse, and social deixis. In this study, 1,903 tokens were found from various lexemes and deixis types. Of the total, 1,478 tokens can be identified as belonging to the category of person deixis. There are 79 tokens in the category of place deixis, 60 tokens in the category of time deixis, 259 tokens in the category of discourse deixis, and 27 tokens in the category of social deixis. It can be concluded that person deixis is more dominant than other types. Based on the analysis, character P1 most frequently uses each type of deixis in the movie Spiderman: No Way Home. P1 uses 748 person deixis, 30 time deixis, 34 place deixis, 137 discourse deixis, and 20 social deixis, with a total of 969 tokens. The use of a person, place, time, discourse, and social deixis in the film Spiderman: No Way Home is properly used as their function. After analyzing the use of words and phrases related to these aspects in the context of the movie, there is nothing inappropriate. Thus, based on the analysis of the use of a person, place, time, discourse, and social deixis in the film Spiderman: No Way Home, it can be concluded that the characters' uses have been by their functions, none of which are deviant.